World food strategy for the 1980s: context, objectives, and approach. - Mellor, John W. (1979)
If food production and consumption trends continue at present levels, Third World countries will face a major deficit in staple food crops by 1990. Requirements to close this food gap include: increased financial assistance; improvements in all traditional approaches to agricultural growth; implementation of existing technology, such as multiple cropping and irrigation; and expanded research concerning food production. Implementation of these efforts will require cooperation from developed and underdeveloped countries alike. Failure in the effort to close the food gap will lead to conflict between the developed countries and the Third World.